Marin’s Resilience as a Victim of Sexual Violence in Rules for Being a Girl (2020) - Jennifer Ivane Simen; Angelika Riyandari (Dinamika Bahasa dan Budaya, 2023)
Sexual violence can happen to anybody, including young people. This article discusses the unwelcome sexual advance experienced by the main character in Rules for Being a Girl novel named Marin. It aims to find out the factors and processes that help Marin to develop resilience and not fall into negative psychological condition of being depressed or traumatic after the sexual violence incident. The theory used to help analyze the development of resilience in Marin is Ungar et al. and Pessoa et al. The results of the analysis are that there are six factors and processes that enable Marin to develop resilience. They are the access to material resources, the supportive relationships, the understanding of her identity, the power and control, the feeling of social justice, and the desire to create a better environment for others. The analysis also shows that Marin is supported by her school that provides rooms to do meaningful and altruistic activities.